Mistar Kalender dalam Pengembangan Khazanah Instrument Falak - moelki-123, Moelki Fahmi Ardliansyah (Universitas Islam Negeri Mataram, 2022)
Calendars by humans are used to mark the change of days and dates. Basically the calendar refers to the movement of celestial bodies. For example, the Gregorian calendar is a calendar that refers to the movement of the Sun. At this point, actually knowing the date on the calendar can be through solar observations, but of course you need a tool. In this study trying to build a celestial instrument to determine the date on the Gregorian calendar called the Mistar Kalender. Furthermore, this study tries to analyze the extent of its accuracy as well as its advantages and disadvantages. This study uses a mixed method combining library and experimental methods with descriptive analysis and numerical analysis approaches where data collection is done through documentation and numerical experimental results. The result of this research is that the Calendar Ruler is built on the concept of the position of the Sun at the local celestial meridian by utilizing a stick/gnomon which will form a shadow length of different sunlight each day. The results of the numerical test carried out showed that the length of the gnomon affected the placement of the sign for the date. The disadvantage of this instrument is that it is local according to the coordinates of the place of observation and depends on the weather at the time of observation. The advantage is as a celestial education medium to make it easier to understand the concept of the Gregorian calendar from the position of the Sun when it is in the local sky meridian.Keywords: Calendar Ruler, Gnomon, Astronomical Instruments